Low-temperature water-assisted crystallization approach to MOF@TiO2 core–shell nanostructures for efficient dye removal. Issue 11 (4th May 2022) - Bao, Shouxin; Lv, Mingyang; Zhao, Chen; She, Ping; Lei, Zhenyu; Song, Xiaowei; Jia, Mingjun
Abstract : A mild crystallization approach to MOF@TiO2 core–shell nanostructures for the efficient adsorption and photodegradation of anionic dyes. Abstract : Metal–organic frameworks (MOFs) have shown excellent adsorption and degradation performance towards different kinds of dyes but suffer problems in the desorption process, where adsorbates cannot be completely removed and may cause energy waste or secondary pollution by the repeated washing with eluent, as well as their relatively weak stability in aqueous solutions. Thus, it is very attractive to integrate MOFs with active ingredients to prepare MOF-based composites with dye adsorption and degradation ability. The reported fabrication method of MOF@TiO2 usually involves high crystallization temperature or contains acid or base additives, which are unfriendly to MOF structures. Here, we report the design of MOF@TiO2 core–shell nanostructures via a surfactant-free amorphous TiO2 coating followed by water-assisted crystallization at a low temperature (100 °C) below the decomposition temperature of most MOFs. Owing to the mild crystallization conditions, MOF cores are maintained and TiO2 shells crystallize to an active anatase phase. The obtained MOF@TiO2 core–shell nanostructures showed excellent dye removal efficiency and stability for anionic dyes, which can remove 98% dye after five adsorption and photodegradation cycles due to the synergistic effect of MOF cores and TiO2 shells. The design concept and synthetic strategy via the water-assisted crystallization method for labile MOF materials encapsulated in functional TiO2 shells may be used to construct other multifunctional MOF core–shell nanostructures, broadening their applications in diverse fields.